Multi-isotope variation reveals social complexity in Viking Age Norway - Lisa Mariann Strand; Sam Leggett; Birgitte Skar (iScience, 2022)
Summary: Multi-isotope studies from human remains from Viking Age graves throughout Norway allow for a deeper understanding of mobility, livelihood, and social organization during the Viking Age (750–1050 CE). Based on a framework of radiocarbon dates (14C), the studied inhumation graves are distributed across a broad chronological and geographical scope, covering the Late Iron and Viking Age (c. 500–1050 CE). Results of multi-isotope analyses (δ18O/δ13C/δ15N) in tandem with a cultural historical approach question the hegemonic masculinity associated with the “violent Vikings” and the apparent preconception of stationary women and mobile males in Viking Age Norway, thus challenging conjectural behavioral distinctions between women, men, and children. The analysis points towards diversity following a north-south gradient in terms of dietary preferences (δ13C/δ15N), which demonstrates a higher degree of marine consumption in northern Norway, as opposed to the southern regions; similar patterns are also observed through the mobility study (δ18O), which uncovers high levels of migration in the study population.